Astell and Masham on Epistemic Authority and Women's Individual Judgment in Religion - Pearce, Kenneth (Oxford University Press, 2022)
In 1705, Mary Astell and Damaris Masham both published works advocating for women’s use of individual judgment in matters of religion. Although both philosophers advocate for women’s education and intellectual autonomy, and both are adherents of the Church of England, they differ dramatically in their attitudes to religious authority. These differences are rooted in a deeper disagreement about the nature of epistemic authority in general. Astell defends an interpersonal model of epistemic authority on which we properly trust testimony when the testifier is answerable for its truth. Masham holds an evidence model of epistemic authority on which testimony is treated as an ordinary piece of empirical evidence. Central to Masham’s argument is her contention that religious beliefs based on the kind of authority recognized by Astell could never serve as a stable source of moral motivation. Because of their different theories of epistemic authority, Masham’s defense of women’s intellectual autonomy leads to a radical anti-clericalism, while Astell’s defense is fully consistent with her insistence on deference to the established church.
Oxford Studies in Early Modern Philosophy Volume 11
Keywords: Religion; Women; Church of England; Epistemic authority; 18th century philosophy; Epistemology; FEMINISM; Philosophy of religion